Morphological and molecular identification of seahorses (Hippocampus spp.) from the coast of Sumatra Island, Indonesia - Fadiyah Hanifaturahmah; Dyah Perwitasari-Farajallah; Nurlisa Alias Butet; Mala Nurilmala; Agus Oman Sudrajat; Yoshihiro Ochiai (Society for Indonesian Biodiversity, 2020)
Abstract. Hanifaturahmah F, Perwitasari-Farajallah D, Butet NA, Nurilmala M, Sudrajat AO, Ochiai Y. 2020. Morphological and molecular identification of seahorses (Hippocampus spp.) from the coast of Sumatra Island, Indonesia. Biodiversitas 21: 4116-4123. Seahorses (Hippocampus spp.) species are difficult to be identified based on their color, shape, and body size, especially for their juveniles. The purposes of this study were to identify seahorse species from Indonesian waters (Riau Islands and Lampung, Sumatra Island) based on the sequence variations in the 16S rRNA and COI genes and to analyze the kinship of these seahorses. The morphological identification was performed, followed by the validation of the identification based on a molecular approach. Both identification methods showed the one species from Riau Islands was H. kuda, while the others (n=2) were H. comes. All specimens from Lampung (n=3) were H. comes. The specimens of H. comes from Riau Islands and Lampung were the same haplotype based on the 16 S rRNA sequence. Based on the COI, H. comes from Riau Islands (n=2) were found to be one haplotype (haplotype 1; n=2), while those from Lampung (n=3) consisted of two haplotypes (haplotype 1; n=2 and haplotype 2; n=1). Phylogenetic analysis based on both genes revealed that H. comes from Riau Islands and Lampung belongs to the same clade, while H. kuda from Riau Islands (n=1) was included in the lineage B (Indian Ocean).